Gololobovia gen. nov. – a new genus from Lake Baikal with comments on pore occlusion in monoraphid diatoms. Issue 6 (1st November 2020) - Kulikovskiy, Maxim; Glushchenko, Anton; Kuznetsova, Irina; Genkal, Sergei; Kociolek, John Patrick
ABSTRACT: A new diatom genus, Gololobovia gen. nov ., is described from ancient Lake Baikal on the basis of light and scanning electron microscopy of its valves. The new genus has a single raphe per frustule and can be assigned to Achnanthidiaceae. Two species are described as new for science from Lake Baikal. These are Gololobovia mariae sp. nov . and Gololobovia baicalensis sp. nov . These species share all of the morphological features typical for the new genus, including uniseriate striae with internal pore occlusions, presence of slightly sinusoid raphe, and an asymmetric axial area that expands into a stauros to form the central area, similar to those in the genera Lemnicola and Gogorevia . Based on the presence of a stauros, uniseriate striae, and the same type of pore occlusions, we speculate that our new genus is more closely related phylogenetically to the above-mentioned monoraphid genera. A type of pore occlusion in the genera Lemnicola, Gogorevia and Gololobovia gen. nov . is discussed. New taxonomic combinations are proposed for Eucocconeis onegensis and Stauroneis obliqua, which are here transferred to our new genus.